St. Victorinus’ doctrine of power and state - Vladimir Vasiik (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2021)
This article deals with the doctrine of power of St. Victorinus of Pettau, the prominent Latin exegete of the 3rd c. and the author of the fi rst preserved commentary on the Apocalypse. The article looks at the level of his education, his intellectual horizon, the general trends of his works as well, his general knowledge of life and his political experience. It studies the issue of the wars and persecutions mentioned in the Commentary and proposes a hypothesis that the Commentary could have been written within the wide interval between 252 and 304. It is shown that in terms of theology St. Victorinus depends on the school of Asia Minor and is estranged from the conception of the symphony of the Roman Empire and the Church, which is present in its germinating form in St. Melitonus of Sardes. In spite of the links with the legacy of Tertullianus, he lacks the idea of the Roman state as the defense wall against Antichrist. On the contrary, the Antichrist concentrates the Roman power with its unlawfulness and crime because he is the resurrected Nero. The latter is, on the one hand, a symbol of the impious pagan Rome with its deifi cation of Man and, on the other hand, the symbol of the union of Jews and pagans directed against Christ and the Church. The image of Nero is connected with a certain numerology: the resurrected Nero will be the eighth emperor and the Antichrist; he will be the king of Jews and, at the same time, of the pagans, the most sordid and hideous parody of the resurrected Christ, his reign being the caricature of the eighth day of eternal life and glory of Christ. This image partly overlaps with the tradition refl ected in Commodianus, partly diff ers from it. The spiral model of history used by St. Victorinus is related to the theology of recapitulation, when one similar event precedes the following, which, in turn, takes places on a higher level. This allows one to suppose the presence of the idea of the “returning Nero”, when every eighth emperor is the forerunner of the resurrected Nero and, accordingly, of the Antichrist. This series includes the persecutors of the Christians: Traianus, Septimius Severus, Decius. The last in this series in Diocletianus, who almost completely corresponds to the features of the “resurrected Nero”, i.e. he comes from the East, kills three kings, behaves as an actor and hypocrite, and, most importantly, is the most ruthless persecutor of Christians of all the Roman emperors. The presence of his co-ruler Galerius may suggest an analogy with the false prophet of Antichrist, i.e. the Second Beast of the Revelation. The true power for St. Victorinus is theocracy, the reign of Christ, who is the only true king over heaven and the earth, and of Saints, who will co-reign with Christ.